The Effect of Working Capital, Business Scale, and Labor on the Income of Dairy Farmers in Boyolali Regency - Wulandari, Wulandari; Susilowati, Heni (CV. Civiliza Publishing, 2025)
This study aims to analyze the influence of working capital, business scale, and labor availability on the income of dairy farmers in Boyolali Regency. This study applies a quantitative descriptive and analytical approach with a sample of 60 dairy farmers who are members of the Cepogo Cooperative (KUD) taken using a purposive sampling method. Data were collected through questionnaires, interviews, observations, and documentation, then analyzed using multiple linear regression using the SPSS program. The findings of this study describe that